Visual Identity Nimade Donuts Sebagai Media Promosi Di Kota Malang - Meydina Dyning Pertiwi; Elfa Olivia Verdiana (Lembaga Penelitian Pengembangan dan Pengabdian Kepada Masyarakat STMIK Asia Malang, 2022)
This research discusses visual identity as a promotional medium because Nimade Donuts does not yet have a visual identity so that customers have difficulty knowing this brand.In this study, Nimade Donuts strives to use more efficient promotional media by making logos, packaging, business cards, posters and x-banners. This promotional media will later become one of the print media used and placed in the Nimade Donuts store.The Nimade Donuts logo that is applied to acrylic will later become a sign system that is placed in front of the Nimade Donuts store to make it easier for customers. Of the questionnaires distributed to 30 respondents as much as 90,78% stated that the selection of visual identity and photo promotion media strongly agreed and was in accordance with the target market so that with the existence of visual identity and promotional media this had answered the problem formulation. Keywords: Nimade Donuts, visual identity, branding, promotion media, Malang city